ANALYSIS AND DESIGN OF SHEAR WALL FOR HIGH RISE BUILDING (G+10) USING STAAD PRO - G.SANTOSH,; V. BHARGAVI, (International Journal of Innovations in Engineering Research and Technology, 2021)
Shear wall is the most commonly used to resist lateral force like wind and seismic loads etc. Shear walls has very high stiffness and strength which provide stability to the structure. The scope of the work is to study of different stories of building with and without shear wall, considering different wind load at different heights and lateral moment of the structure with and without shear wall.Wind load will be applied to building for G+10 on different cases of shear wall position. An analysis and design will be performed using STAAD Pro software. Shear walls are generally usedin high wind loads areas, as they are highly efficient in taking the loads. Notonly have the wind loads also resists earthquake loads which are quite high in some zones can be taken by these shearedwalls effectively and efficiently.Construction made of shear walls are high in strength they majorly resists the wind loads and seismic loads even can be builton weak soil bases by adopting various ground improvement techniques. Not only the strength and effectiveness to be bare horizontal loads is very high and also increase the quickness in construction process.